A single-tube multiplex PCR for rapid detection in feces of 10 viruses causing diarrhea - Khamrin P. (2014)
A novel multiplex polymerase chain reaction assay was developed to identify 10 viruses in a single tube. The assay was targeted to detect group A and C rotaviruses, adenovirus, norovirus GI, norovirus GII, sapovirus, astrovirus, Aichi virus, parechovirus, and enterovirus. A total of 235 stool samples were collected from infants and children with acute gastroenteritis in Kyoto, Japan, from 2008 to 2009, then tested by this novel multiplex PCR and compared with a multiplex PCR described previously, which used 3 primer sets. The novel multiplex PCR could detect the targeted viruses in 111 of the 235 (47.2%) stool samples. Of these, 9 out of 10 types of viruses were identified, including group A rotavirus, norovirus GII, enterovirus, sapovirus, adenovirus, parechovirus, group C rotavirus, astrovirus, and norovirus GI. In contrast, the multiplex PCR that used 3 sets of primers could detect the targeted viruses in 109 of the 235 (46.4%) stool samples. Among these, 8 types of viruses were identified, including group A rotavirus, norovirus GII, enterovirus, adenovirus, parechovirus, group C rotavirus, sapovirus, and astrovirus. The results suggested that the new multiplex PCR is useful as a rapid and cost effective diagnostic tool for the detection of major pathogenic viruses causing diarrhea. © 2011 Elsevier B.V.